Pengaruh Green Marketing dan Brand Image terhadap Keputusan Pembelian Produk Garnier pada Mahasiswa STIE IBMT Surabaya - Suliyanfi Garnis Diah Pitaloka; Iswati Iswati; Anis Fitriyasari; Suyono Suyono (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The purpose of this study is to determine the effect of green marketing and brand image on consumer decisions to buy Garnier products. This study uses a quantitative research approach, and data collection is done through a questionnaire that is given a Likert score of 1-4. This research involved students or female students of STIE IBMT. The sampling technique used is purposive sampling, or nonprobability. This study used 94 respondents. In this study, primary data was used, and the data analysis method used was multiple linear regression analysis. This was done with the help of statistical data analysis tools. The analysis method uses descriptive test, validity test, reliability test, multiple linear regression analysis, hypothesis testing, and classical assumption test. The results showed that there is a green marketing influence on purchasing decisions for garnier products. Then there is also the influence of brand image on purchasing decisions for garnier products, and there is also an influence between green marketing and brand image on purchasing decisions for garnier products. From this research, it is hoped that it can develop other factors or variables that can influence green marketing and brand image on product purchasing decisions with other environmentally friendly brand products.